Effect of Liquidity Ratio, Solvability, Asset Growth and Inflation on Stock Return with Profitability as Intervening Variable at Building Construction Sector in Indonesian Stock Exchange: A Review of Theories and Evidence - Eskilani, El Cindy; Kisman, Zainul; Sawitri, Ni Nyoman (Archives of Business Research, 2019)
The companies have the main goal is to maximize the value of the firm by increasing net income and stock returns to shareholder wealth. Stock returns is a rewards and results in the form of profits or losses obtained from stock. The level of return obtained by investors is influenced by microeconomic and macroeconomic factors. The question is from many factors that affect stock returns, what factors are more influential on the building construction companies where has listed on the Indonesia Stock Exchange from the 2014-2018 period. The purpose of this study was to determine the effect of microeconomic and macroeconomic factors to stock return by reviewing theories and empirical evidence. After reviewing many theories and literature including some prior research, finally, this study reaches conclusions that there are some variables like liquidity, solvability, profitability, asset growth even inflation influence the stock return of the company.